Agricultura em cidades Maias, Astecas e Incas: outra perspectiva sobre o urbano - Rinaldo de Castilho Rossi (Confins)
This text aims to contribute to the theoretical debate on the concepts of city and urban, based on the analysis of the material and symbolic relevance of agriculture in the former agglomerations of Caracol, (Maia), Tenochtitlán (Aztec), Machu Picchu and Ollantaytambo (Inkas), highlighting their respective archaeological and historiographic evidences and theses. In addition to making considerations about food production systems, the following theoretical and methodological aspects are discussed based on the cases studied: (a) applicability of the concepts of city and urban to the study of pre-colonial societies in America; (b) the role played by the center on promoting agriculture; (c) agriculture as a technology of urbanism towards adversity; (d) relevance of Abya Yala’s native cities study. This research was based on four methodological steps, that included bibliographic review about city and urban space, as well as specific publications on the cases cited. The evidence highlighted in this paper emphasizes the need to decolonize theoretical concepts and recognize urban agriculture as an ancient and current strategy to deal with past and present challenges.